Common variants of IRF3 conferring risk of schizophrenia. (May 2015) - Li, Xiao; Zhang, Wen; Lencz, Todd; Darvasi, Ariel; Alkelai, Anna; Lerer, Bernard; Jiang, Hong-Yan; Zhang, Deng-Feng; Yu, Li; Xu, Xiu-feng; Li, Ming; Yao, Yong-Gang
Abstract: Schizophrenia is a brain disorder with high heritability. Recent studies have implicated genes involved in the immune response pathway in the pathogenesis of schizophrenia. Interferon regulatory factor 3 ( IRF3 ), a virus-immune-related gene, activates the transcription of several interferon-induced genes, and functionally interacts with several schizophrenia susceptibility genes. To test whether IRF3 is a schizophrenia susceptibility gene, we analyzed the associations of its SNPs with schizophrenia in independent population samples as well as reported data from expression quantitative trait loci (eQTL) in healthy individuals. We observed multiple independent SNPs in IRF3 showing nominally significant associations with schizophrenia ( P < 0.05); more intriguingly, a SNP (rs11880923), which is significantly correlated with IRF3 expression in independent samples ( P < 0.05), is also consistently associated with schizophrenia across different cohorts and in combined samples (odds ratio = 1.075, P meta = 2.08 × 10 −5 ), especially in Caucasians (odds ratio = 1.078, P meta = 2.46 × 10 −5 ). These results suggested that IRF3 is likely a risk gene for schizophrenia, at least in Caucasians. Although the clinical associations of IRF3 with diagnosis did not achieve genome-wide level of statistical significance, the observed odds ratio is comparable with other susceptibility loci identified through large-scale genetic association studies on schizophrenia, which could be regarded simply as small but detectable effects. Highlights: We identified an eQTL SNP associated with IRF3 expression in independent samples. The eQTL SNP was associated with schizophrenia in independent samples. The schizophrenia samples were from different ethnics, and the sample size was relatively large. IRF3 is an important gene in immune system, and our data further supports the immune hypothesis of schizophrenia.